Refractive Outcome in Preterm Newborns With ROP After Propranolol Treatment. A Retrospective Observational Cohort Study - Filippi, Luca; Cavallaro, Giacomo; Perciasepe, Lavinia; Sandini, Elena; Araimo, Gabriella; Regiroli, Giulia; Raffaeli, Genny; Bagnoli, Paola; Dal Monte, Massimo; Calvani, Maura; Fortunato, Pina; Osnaghi, Silvia; et al. (Frontiers in Pediatrics, 2019)
Background. Recent explorative studies suggest that propranolol reduces retinopathy of prematurity (ROP) progression, but the short-term effects of propranolol treatment at one year of corrected age have not been extensively evaluated. Methods. A multi-center retrospective observational cohort study was conducted to assess the physical development and the refractive outcome of infants with prior ROP treated with propranolol. Forty-nine infants treated with propranolol were compared with an equal number of patients who did not receive any propranolol therapy and represent the control group, with comparable anthropometrical characteristics and stages of ROP. Results. The weight, length, and head circumference at one year of corrected age were similar between infants who had been treated, or not, with propranolol, without any statistically significant differences. Refractive evaluation at one year showed spherical equivalent values decreasing with the progression of ROP towards more severe stages of the disease, together with an increasing number of infants with severe myopia. On the contrary, no differences were observed between infants who had been treated with propranolol and those who had not. Conclusion. This study confirms that the progression of ROP induces an increase of refractive errors and suggests that propranolol itself does not affect the refractive outcome. Therefore, if the efficacy of propranolol in counteracting ROP progression is confirmed by further clinical trials, the conclusion will be that propranolol might indirectly improve the visual outcome, reducing the progression of ROP.